Preparation of activated alumina From Iraqi-kaoline clays for Catalysts support (Baghdad Science Journal, 2025)
In this work the activated alumina was extracted from Iraqi- kaoline clays by sintering lime method as first stage to produce the fine powder and then using this powder to prepare high purity of an activated alumina (99%Al2O3)and surface area around 205m2 /gm which used in the petrol and petro chemical industries to remove the sulfur and absorption acidic gasses and as benzene improvement The preparation mothed washing operation and remove the impunities , temperature effect and burning time were studied as well .